The degree of availability of the dimensions of intellectual security in the language competencies course for the secondary stage in the Kingdom of Saudi Arabia - Al- Hujaili, Hanaa Mansour Fawaz; Al- Tunisi, Nabila Taher Ali (Journal of Educational and Psychological Sciences, 2022)
This study discusses the degree of availability of the dimensions of intellectual security in the language competencies course for the secondary stage in the Kingdom of Saudi Arabia. The descriptive- analytical approach was applied using four main dimensions of intellectual security, including the religious dimension, national dimension, social dimension, and scientific thinking dimension. Thirty- four security indicators were found, and based on them; a design content analysis card was created. The content analysis card was applied to the study population of the language competencies course for the first grade of secondary school in the two semesters after ensuring the validity and stability of the card. The results of the study: the degree of availability of indicators of the religious dimension and the dimension of scientific thinking in the language competencies course was low, while the social dimension and the national dimension had a deficient degree. The language proficiency course was generally balanced in its inclusion of indicators of the dimensions of intellectual security as they were repeated in the first semester 202 times. In contrast, they were repeated in the second semester 211 times. Several recommendations are initiated based on the results, such as guiding and directing those in charge of preparing and developing academic courses on how to include indicators of the dimensions of intellectual security to enhance its consolidation among students. In addition, provide training courses for the teachers to instill intellectual security dimensions in students’ minds and acquire them in proportion to the secondary stage. Moreover, to provide scientific workshops and awareness seminars for the students; to make them aware of the national visions in general and the 2030 vision in particular.